Alternativas para o tratamento do superendividamento bancário e a proteção do mínimo existencial do consumidor - COSTA, André Felipe dos Santos (2020)
Given the need to define a method for the treatment of over indebtedness in Brazil, given the absence of legislation on the subject, the present work addresses the alternatives for the treatment of this social problem, exported from models used in other countries, the search for a model that fits the guarantees of minimum stocks of the over-indebted consumer. Therefore, it is necessary to situate the position of the national doctrine about consumer indebtedness, to establish a concept of existential minimum to guide a system of treatment of over indebtedness and to discuss the models for treatment of over indebtedness, in order to establish a proposal that contemplates the minimum. existential A bibliographical, exploratory and qualitative research is then conducted, having as main sources the doctrines, articles, legislations, jurisprudence and statistical data. Given this, it appears that the concept of over-indebtedness in national doctrine is based on the French social model, and the existential minimum is a fundamental premise of the entire Brazilian legal system and none of the models developed in comparative law, nor the revision contracts, are able to contemplate the consumer protection system, which requires the realization that a third way is necessary for the adaptation of the over-indebted consumer treatment models to the socio-legal reality of the country.